Longevity of direct resin composite restorations in maxillary anterior crown fractures: A 4-year clinical evaluation - KORKUT, BORA (My University, 2022)
Objectives To investigate the longevity of direct composites for Class IV restorations and the possible reasons of failure. Methods and Materials The longevity of 168 Class IV restorations in 50 adult patients was evaluated, in terms of modified United States Public Health Service criteria, for 4 years. Restorations were performed using a monochromatic layered microhybrid, resin-based composite (RBC) (Essentia, Universal Shade, GC Corporation, Japan; n=76) and polychromatic layered micro/nanohybrid (MD and LE shades, Essentia, GC Corporation, Japan; n=92) RBCs, by a single operator. Results The majority of the teeth (n=156) remained acceptable at the end of 4 years, and the overall survival (OS) rate was considered as 92.86%. Survival rates for the monochromatic layering technique (MLT) and polychromatic layering technique (PLT) were 90.8% and 94.6%, respectively. Mean survival was 46 months for MLT and 47 months for PLT, indicating no significant difference (p=0.343). Fracture of the restoration was the most common reason for failure (4.2% out of 7.1% of general failures) for both the layering techniques. Conclusions Under the conditions of this mid-term clinical study, MLT and PLT as well as microhybrid and nanohybrid resin composite materials, showed similar clinical durability. In terms of simplicity, monochromatic layering can be preferred for Class IV restorations, when the right indication criteria are met.
Keywords: Tıp; Sağlık Bilimleri; Diş Hekimliği; Medicine; Health Sciences; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry